Initiation of Cardiopulmonary resuscitation by bystanders in Qatar based on the gender of cardiac arrest victims - Emad Awad (17541264) (2024)
Background Out-of-hospital cardiac arrest survival is dependent upon the victim receiving timely and effective cardiopulmonary resuscitation (CPR), however bystanders may be hesitant to apply chest compressions on women. The overall provision of bystander CPR has previously been reported to be 20.6% in Qatar2 but no study reported on gender differences. This study aimed to retrospectively analyse if there was a difference in Qatar in the initiation of CPR based on the patients’ gender. Methods Following institutional ethical approval, data of non-trauma-related cardiac arrest patients in the pre-hospital setting attended to by the Ambulance Service3 in Qatar between 2016 to 2022 was retrieved from the public hospital system. From the information collected, we determined the circumstances when CPR was provided by a layperson before ambulance arrival. Chi-square and student’s t-test were respectively used to determine association between categorical and continuous variables. Results The study included 4,283 patients, out of which 38.3% were female, and they were on average nearly 10 years older than the male patients. Overall, 34.2% received bystander CPR. It was respectively provided to 35.4 % and 29.2% of men and women (p<0.001). It was noticed that most women in Qatar had their cardiac arrest when at home (84.9%) as opposed to being in a public place. Conclusion The study found that, in Qatar, women were less likely to receive bystander CPR than men despite being more prevalent to suffering from cardiac arrest in a home setting and potentially surrounded by people they know. The disproportionate gender and age differences in the study sample can be explained by Qatar’s demographic distribution, which is skewed by a very high number of younger male expatriate workers.2 More public education regarding the importance of immediate and effective CPR by layperson, regardless of the gender, could help improve survival.